A Comparative Analysis of The Economic Importance of Islamic and Conventional Banks in KSA - Alhazmi, Ali Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of the research is to compare the importance of Islamic banks and conventional banks to the economy of the Kingdom of Saudi Arabia, in terms of efficiency, stability and risk management. Economic indicators, based on the references and specialized statistical reports.The superiority of Islamic banks over conventional banks in seven indicators, and the superiority of conventional banks over Islamic banks in three indicators, and their equivalent in two indicators. It was also shown that the ratio of Islamic banks’ investments to GDP increased from one year to another, rising from 0.5% in 2003 to 20.7% in 2021, but the ratio of conventional banks’ investments to GDP declined from one year to another, from 87.1% in 2003 to 81.3 % in 2021.The research recommended the necessity of encouraging the spread of branches of Islamic banks inside and outside the Kingdom, and setting up their own legal and economic legislation to serve their work, and the need to issue temporary instructions that concern the inclusion of Islamic banks in supporting the government sector and investments and with higher rates of participation in development plans, and the need to review the reasons for the superiority of conventional banks over Islamic banks in the previous three indicators, and the necessity of making the subject of Islamic economics taught in Islamic and Arab universities.
Keywords: Islamic banks; conventional banks; financial indicators; bank deposits; profits; liquidity